Philosophical Comprehension of the Psychological and Information Influence Technologies in the Modern World - Atoyan, Vardan; Ohanyan, Sofya; Movsisyan, Nane; Malkjyan, Arpine («Տնտեսագետ» հրատ․)
The concepts of “information influence” and “psychological influence” in the light of the history of philosophy allow us to record that their formation was greatly influenced by the sociocultural transformations that influenced the formation of a new philosophical image of the world, gradually preparing the consideration of such influences as information influence and psychological influence.The supremacy of information technology has created a new reality with new rules. Information warfare between countries and an “information” economy is based on a number of views. Both information and psychological influences play a key role in the above mentioned. Each information influence implies a psychological influence and vice versa: the psychological influence, in turn, becomes the basis for an information influence. In this research, the authors have attempted to make a “3D” observation of the issue. First, the authors highlighted the philosophical foundations of information and psychological influences. Second, they showed the mechanisms that cause information and psychological influences. Third, the issue of information security was brought forward, and the issue of dealing with various means of manipulation was raised. The authors considered the information influence from the point of view of its turning into psychological influence, considering the issue in a new light.
Keywords: History; Philosophy